2021
DOI: 10.1016/j.esmoop.2021.100062
|View full text |Cite
|
Sign up to set email alerts
|

Influence of BRAF and PIK3CA mutations on the efficacy of FOLFIRI plus bevacizumab or cetuximab as first-line therapy in patients with RAS wild-type metastatic colorectal carcinoma and <3 baseline circulating tumour cells: the randomised phase II VISNÚ-2 study

Abstract: Background We explored the influence of BRAF and PIK3CA mutational status on the efficacy of bevacizumab or cetuximab plus 5-fluorouracil/leucovorin and irinotecan (FOLFIRI) as first-line therapy in patients with RAS wild-type metastatic colorectal cancer (mCRC). Patients and methods VISNÚ-2 was a multicentre, randomised, phase II study. Patients with RAS wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Concerning sidedness, our findings emphasize the poor outcome of patients with RCC, compared to those with LCC, as reported in several clinical studies 4 - 6 . The aggressive behavior of RCC has been attributed to a higher occurrence of BRAF mutations 37 , PIK3CA mutations 38 - 40 or CpG island methylation phenotype (CIMP) 41 - 43 , all factors associated with shorter survival 44 - 47 . However, thus far, no study has focused on sex disparities relative to RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning sidedness, our findings emphasize the poor outcome of patients with RCC, compared to those with LCC, as reported in several clinical studies 4 - 6 . The aggressive behavior of RCC has been attributed to a higher occurrence of BRAF mutations 37 , PIK3CA mutations 38 - 40 or CpG island methylation phenotype (CIMP) 41 - 43 , all factors associated with shorter survival 44 - 47 . However, thus far, no study has focused on sex disparities relative to RCC.…”
Section: Discussionmentioning
confidence: 99%
“…In multivariate analysis, patients with a PIK3A mutation and LGR5 expression had poor outcomes for both DFS and OS [ 58 ]. PI3KCA mutations are present in 13% of mCRC cases and are associated with right-sided tumors, older patients, and poor prognosis [ 58 , 59 , 60 ].…”
Section: Targeted Drug Modulation Of Stemness Pathwaysmentioning
confidence: 99%
“…Compared to mFOLFOXIRI alone, mFOLFOXIRI combined with bevacizumab increased the incidence of clinical NED and tended to improve survival. In another study (Visnu-2), which was a multicenter, randomized, phase II study [ 63 ], investigators studied the effect of BRAF and PIK3CA mutation status on first-line treatment with bevacizumab or cetuximab in combination with 5-fluorouracil/calcium folate and irinotecan (FOLFIRI) in patients with RAS wild-type mCRC. The findings suggested that BRAF/PIK3CA status affects the outcomes of patients with RAS wild-type mCRC, but does not appear to contribute to the selection of first-line targeted therapy.…”
Section: Braf Inhibitors and Potential Targeted Therapiesmentioning
confidence: 99%